Effects of public debt on economic growth of East African countries - Fatoki, Olanrewaju; Muoki, Victor (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The purpose of this study was to determine the influence of public debt on economic growth of three east African countries (Kenya, Uganda and Tanzania). Specifically, the study aimed to establish the influence of external concessional public debt, external commercial public debt and domestic public debt on economic growth of the three east African countries. This study applied a causal research design as it sought to assess effect of public debt on economic growth and collect secondary time series data for 57 years (1963 – 2019). Macro panel regression was used to analyze the collected data using the fixed effects model. The study findings established that concessional debt and external commercial debt had a significant positive effect on economic growth, while domestic debt had a significant negative effect on economic growth. Based on this study findings, the study makes the following recommendations. First, the three East African countries should source for more external concessional debt through bilateral or multilateral arrangements to plug into their budget deficits. The study also recommends that the level of domestic borrowing in the three East African countries should be reduced. This is because domestic borrowing is harmful to economic growth of the three countries.